Effect of Extra Virgin Olive Oil on the Apoptosis Index and the Number of Antral Ovarian Follicles in Rats Exposed to Cigarette Smoke - Huda Rohmawati; Nara Lintan Mega Puspita; Pria Sabila Putri; Raras Sucma Ambar (Universitas STRADA Indonesia, 2024)
Infertility is a global problem. Risk factors for infertility are cigarette smoke. Cigarette smoke contains harmful substances that can have adverse effects on follicle development. Oxidative stress due to cigarette smoke can activate proinflammatory cytokines in ovarian blood. Alternative natural treatments are needed that have antioxidant and anti-inflammatory properties. Extra virgin olive oil is pure oil from olives rich in antioxidants. Its polyphenol content has been proven to be high in anti-inflammatory and antioxidant properties. This study aims to determine the effect of extra virgin olive oil on the apoptosis index and the number of antral ovarian follicles in mice exposed to cigarette smoke. The design of this study was a true experiment with a post-test-only control group design. The experimental animals used white mice aged 2-3 months, weighing 150-250 grams.